Moderasi Beragama Dalam Konsep Agama Madani Perspektif JJ Rousseau - Aulia Rahman (UIN Siber Syekh Nurjati Cirebon, 2026)
This article describes religious moderation as the concept of civil religion from Rousseau's perspective. As a philosopher, Rousseau developed a concept known as civil religion. This is highly intriguing when linked to the religious moderation program currently promoted by the Indonesian government. The research method employed in this article is qualitative, utilizing various research approaches, one of which is a literature study that refer to the epistemological paradigm based on the civil religion thought proposed by J.J. Rousseau. Data were collected from journals and other sources related to civil religion and religious moderation to comprehend the goals of civil religion. The data were then examined using interpretative analysis. Based on the findings, it can be concluded that, first, J.J. Rousseau's concept of civil religion is a social framework that emphasizes loyalty to both the state and religion. Consequently, this fosters individuals who are concerned about both their faith and their country, ultimately awakening a spirit of religious nationalism. Second, the religious moderation program aligns with J.J. Rousseau's concept of civil religion when viewed through the four pillars of religious moderation. Therefore, it is concluded that J.J. Rousseau's concept of civil religion contributes to the development of the religious moderation concept applied in Indonesia within the framework of Pancasila.